Risk factors of long-term mortality in middle-aged women: a 27-year follow-up cohort. (2nd November 2018) - Blümel, J. E.; Aedo, S.; Arteaga, E.; Vallejo, M. S.
Abstract: Objective: This study aimed to evaluate the impact of different risk factors on long-term mortality in middle-aged women. Methods: Women who received preventive health care control between 1990 and 1993 were recruited. Anamnesis and physical examination were recorded. Blood samples for the measurement of glycemia and lipids were taken. Data are reported as of December 2017. Results: We studied 1197 women aged between 40 and 60 years. We observed 183 deaths (survival 84.0%; 95% confidence interval [CI], 81.7–86.1, Kaplan–Meier survival analysis). The main causes of death were cancer (39.9%; 95% CI, 32.7–47.1), cardiovascular disease (22.9%; 95% CI, 16.8–29.1), infectious disease (13.7%; 95% CI, 8.6–18.7), other causes (7.1%, 95% CI, 3.4–10.9), and unspecified cause (6.6%; 95% CI, 2.9–10.2). The final Cox regression model showed the following hazard ratios for mortality: diabetes mellitus 2.51 (95% CI, 1.40–4.51), history of fracture 2.47 (95% CI, 1.15–5.30), history of heart illness 2.06 (95% CI, 1.15–3.72), arterial hypertension 1.51 (95% CI, 1.08–2.11), age 1.07 (95% CI, 1.04–1.10), body mass index 1.06 (95% CI, 1.02–1.09), and sexual intercourse 0.94 (95% CI, 0.89–0.98). Lipid disorders did not reach statistical significance as a risk factor. Conclusion: Diabetes, a history of fractures, and cardiovascular risk factors, except lipids, are markers of long-term mortality in middle-aged women. Physicians should pay special attention to these risk factors.